Digestion in the Mouth and Stomach in the Early Postnatal Period - Kamalova Lobar Yagmurovna (Zien Journals, 2023)
The morphofunctional features of the digestive system depend primarily on the type of nutrition and food composition. Adequate food for children of the first year of life, especially the first 4 months, is mother's milk. By the time of the birth of the child, the secretory apparatus of the digestive tract is formed according to milk feeding. The number of secretory cells and enzymatic activity of digestive juices are insignificant. The share of cavitary digestion is much less than in adults. In the first days and months, along with the cavity, an autolytic type of digestion is carried out by breast milk enzymes. The share of parietal and intracellular hydrolysis of proteins, fats and carbohydrates is about 80% of the total volume of digestion
Keywords: Salivary glands; digestion in the stomach; enzymes; bile excretion